Industry 4.0 and its effects on the labour market - Antonín, Adam; Pantea, Smaranda; Bič, Josef; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
The Influence of Industrial Robots on German Employment, 2009–2019 The thesis explores the impact of industrial robots on employment in Germany between 2009 and 2019. sing sector-level panel data and multiple econometric models. Examining both substitutional and compensation effects. The analysis focuses mainly on sectors denoted as NACE 2 sectors mainly industrial. and distinguishes between models including and excluding output (gross value added) to isolate different theoretical mechanisms. The results of the linear regression are consistently showing a positive relationship between robot adoption and sector-level employment. This supports the compensation theory, indicating that robotisation may enhance productivity and stimulate job creation. To support the stability of the results robustness checks and alternative model specifications were introduced. While the main findings show that the adoption of industrial robots has not reduced the aggregate employment. Overall, the thesis highlights the significance of institutional settings in mitigating labour market disruptions and facilitating adaptation to technological change.
Vedoucí práce: Smaranda Pantea
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses